2012
DOI: 10.1175/jcli-d-11-00727.1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Kuroshio in the East China Sea on the Early Summer (Baiu) Rain

Abstract: Influence of the Kuroshio in the East China Sea on the baiu rainband is examined using satellite observations, a reanalysis dataset, and a regional atmospheric model from 2003 to 2008. Satellite observations and reanalysis data reveal that precipitation over the Kuroshio is the highest in early summer (June), when the baiu rainband covers the East China Sea. The high rainfall is collocated with the warm sea surface temperature (SST) tongue of the Kuroshio. This locally enhanced precipitation is embedded in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
88
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(101 citation statements)
references
References 48 publications
12
88
1
Order By: Relevance
“…Strong updrafts occurred in the ECS during the target period and were strongest at 400 hPa. This observation was consistent with a previous report (Sasaki et al, 2012). Figure 1c shows the mean relative humidity of the MSM at 400 hPa.…”
Section: Mean Atmospheric Conditions and Cloud Properties In The Ecssupporting
confidence: 93%
See 1 more Smart Citation
“…Strong updrafts occurred in the ECS during the target period and were strongest at 400 hPa. This observation was consistent with a previous report (Sasaki et al, 2012). Figure 1c shows the mean relative humidity of the MSM at 400 hPa.…”
Section: Mean Atmospheric Conditions and Cloud Properties In The Ecssupporting
confidence: 93%
“…Evaporation from the sea surface in the Kuroshio region enhances the formation of convectively unstable air masses, which can produce deep convection Tsuguti and Kato, 2014;Manda et al, 2014;Kunoki et al, 2015;Sato et al, 2016). The Kuroshio also impacts the surface wind convergence, which in turn helps form the deep convective clouds (Xu et al, 2011;Sasaki et al, 2012;Miyama et al, 2012). Recent studies reported the impact of the Kuroshio on the cloud vertical structure.…”
mentioning
confidence: 99%
“…3a). This correspondence of the positions of the Baiu frontal zone and the Kuroshio Front in May is consistent with several recent studies (Xu et al 2011;Sasaki et al 2012;Miyama et al 2012).…”
Section: Seasonal Migration Of the Baiu Frontal Zone Over The East Chsupporting
confidence: 92%
“…The North Atlantic and North Pacific WBCs, the Gulf Stream, and KuroshioOyashio Extension (KOE) influence the atmosphere through the entire troposphere during spring and summer (Minobe et al 2008(Minobe et al , 2010Xu et al 2011;Sasaki et al 2012) and modify low-level atmospheric baroclinicity, shifting the free-tropospheric storm track and altering the poleward heat and moisture transport (e.g., Tokinaga et al 2009;Frankignoul et al 2011;Ogawa et al 2012;Taguchi et al 2012;Kwon and Joyce 2013;O'Reilly and Czaja 2015). In the Southern Ocean, south of the Indian Ocean, the Agulhas Return Current (ARC) helps to anchor the climatological location of the free-tropospheric storm track (Nakamura et al 2004).…”
Section: Introductionmentioning
confidence: 99%